THE ROMANIAN POPULATION BY GENDER AND AGE GROUPS IN 2011 - POP, Gr. P.; ZOTIC, V.; ALEXANDRU, Diana Elena (Studia Universitatis Babeș-Bolyai Geographia, 2015)
The Romanian Population by Gender and Age Groups in 2011. Following the previous studies on the demographic characteristics of the Romanian population, ethnicity and religion, this study covers the geodemographic issues of gender and age groups. As compared to the previous studies, our analysis covers these major population features in strong connection with the numerical evolution of the population, strongly determined by the socioeconomic background before 1990 and afterwards. We used the official data of the census in 2011 provided by the National Institute of Statistics. In order to create a representative picture of the Romanian population by gender and age groups, we employed the data illustrating the state of these two indicators in tables and maps. As compared to the values registered in 1992, the Romanian population in 2011 registered a decrease of 11.79%, relatively balanced in terms of gender structure, the male population holding a share of 48.65% and the female population, a share of 51.35%. The age structure also reveals a relative balance between active adult population (56.32%) and the young and old population, together holding a share of 43.68%. Spatially, the structure of the Romanian population by gender and age structure, show differences at county level and also at a larger scale.